Exclusive Breast Feeding and Reasons of its Failure in Infants Less Than 6 Months of Age (Medical Forum Monthly, 2024)
Objective: To know the frequency of exclusive breast feeding and the reasons given by the mothers for not practicing 'exclusive breast feeding'.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Children Outdoor of Bahawal Victoria Hospital, Bahawalpur from July to September 2016.Methods and Materials: 200 mothers visiting the Children Outdoor with infant less than six months of age were interviewed.Results: 200 mothers were interviewed. 89.5% of them were housewives while 10.5% were working ladies. 43.5% mothers were having monthly family income less than 10000, 46% with 10000-49000 and 10.5% with 50000 rupees or more. 18% infants were given colostrum as first feed while the 14.5% infants were put on breast milk within one hour of birth. 26.5% infants were exclusively breast fed while 73.5% were belonging to the group of 'not exclusively breast fed’. The three most common reasons included ‘mother milk is insufficient (59.2%)’, ‘mother feels baby is weak (14.3%)' and ‘she is a working lady (11.6%)'.Conclusion: The exclusive breast feeding practices are poor and three common reasons are maternal perception of having insufficient milk, mothers feeling baby is weak/ill and mothers are working ladies.